Rand McNally world map for the air age, ed. by George T. Renner - Rand McNally and Company (Special Collections and College Archives, Gettysburg College, 2015)
Chicago 1943 Inset: Antarctica; Prime meridian: Greenwich; Air line distances shown in statute miles; "11R442."; "AOW913." Shows principal world airlines, operating and proposed lines as of 1939